Analysis of Science Teachers' Understanding of High Order Thinking Skills (HOTS) and Their Implementation in Learning - Desak Made Anggraeni; Ferdinandus Bele Sole (Postgraduate, University of Mataram, 2020)
This study aims to analyze and describe data on the understanding of YAPNUSDA elementary school teachers of High Order Thinking Skills (HOTS) and their implementation in learning. This study is a descriptive study that describes HOTS's understanding of the teacher and its implementation in learning. The data collection tool used was a questionnaire. The results of this study indicate that in general the data obtained is that the teachers in the study location schools do not yet understand about HOTS. They can't even explain the definition of HOTS. The lack of understanding of HOTS certainly has an impact on the implementation of HOTS in the tools for assessing learning performance, including the exam questions jointly prepared by the editorial team. The most frequently cited reason that also hinders teachers is that they do not yet understand HOTS and the technique of formulating instruments with verbs that measure HOTS.